The Effect of Product Quality on Customer Loyalty with Customer Trust and Customer Satisfaction as Intervening Variables in Using Consumer Credit at Bank BJB - Surabaya Branch Office - Purwanto, Eko; Hapsari, Fani Rachma (Nusantara Science and Technology Proceedings, 2020)
The study of marketing strategies on improving product quality carried out by Bank BJB was carried out to examine whether this creates a sense of trust and customer satisfaction to make them loyal customers in using BJB bank products. Consumer loans are loans that are consumptive for permanent employees with payment from income. The sample in this study were 98 consumer credit customers at Bank BJB - Surabaya Branch took by simple random sampling technique and the calculation of the Slovin formula. The research data consisted of primary and secondary data. Primary data was obtained from questionnaires and secondary data was obtained from the company. The analytical tool used in the present research was Partial Least Square (PLS). The results of this study indicated that product quality contributed to customer satisfaction and trust and resulted in inconvenience to customers. Customer satisfaction and trust contributed to customer loyalty.